The Dynamics of SARS-CoV-2 (RT-PCR) Testing - Nicole Joyce; Lynsey Seim; Michael Smerina (Case Reports in Medicine)
The COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is estimated to have affected 6.2 million people in the United States and 27.5 million people worldwide as of September 9, 2020. On February 2, 2020, the Secretary of the Department of Health and Human Services (HHS) determined that the public health emergency justified the development and emergency use of “in vitro diagnostics for the detection and/or diagnosis of the virus that causes COVID-19” by activating the Emergency Use Authorization (EUA) authority under section 564 of the Federal Food, Drug, and Cosmetic Act. Unfortunately, effective mitigation efforts were thwarted early in the outbreak resulting in an expansion of the initial EUA on February 29, 2020, to improve accessibility to in vitro diagnostic testing. Expectantly, the development and deployment of SARS-CoV-2 testing including RT-PCR expanded rapidly in the weeks following the EUA expansion. These newly developed and approved SARS-CoV-2 RT-PCR tests boast impressive positive and negative agreement rates nearing 100%. Despite the exceptionally high rates of agreement, caution is advised as the RT-PCR tests approved under the COVID-19 EUA are in vitro analyses developed with samples artificially doped with SARS-CoV-2 RNA. These tests therefore do not have clinically applicable sensitivity and specificity because they lack a “gold standard” for diagnosis. Here we present three challenging cases requiring cautious interpretation of the newest generation of RT-PCR molecular detection assays, highlighting the major challenges faced by providers treating patients potentially infected with SARS-CoV-2.